Impact of Community-Based Medical Student Engagement on Polio Immunization Uptake in Underserved Populations: A Cross-Sectional Study - Saher Sultan, Zubair Ahmed, Jai Dev Maheshwari, Aftab Hussain Abro, Renad Al Mefleh, Majid Hafeez Qadri, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Persistent immunity gaps in underserved communities continue to threaten polio eradication efforts in Pakistan. Innovative community engagement strategies are needed to improve vaccine uptake and address knowledge and trust deficits. Purpose: To determine the relationship between community-based medical student interest and complete polio immunization rates amongst children aged 059 months in underserved areas of Pakistan. Methodology A community-based cross-sectional study was carried out from December 2022 to May 2023 in 24 clusters (12 intervention, 12 comparison). Eight hundred caregivers (400 in each group) were interviewed by using the multistage cluster sampling method. A dependent variable was the intervention which consisted of supervised medical student outreach in the form of household visit, health education and provision of immunization services. The main result was age-based polio immunization based on the national schedule. Data analysis was done by a chi-square and multivariate logistic regression that controlled the socio-demographic variables and variables on access. Result: Intervention clusters showed high rates of full polio immunization as opposed to comparison clusters (86.0% vs 71.0%, p<0.001). With adaptation, medical student engagement exposure was still found to be independently related with full immunization (adjusted OR 2.08; 95% CI 1.433.02). Vaccination intervention clusters also had better caregiver knowledge and trust in the source of vaccine information. Conclusion: Community-based medical student intervention showed a positive effect on polio immunization coverage and positive caregiver attitudes, making it possible to consider its use as a supplementary intervention to enhance routine immunization in underserved areas. Keywords: polio immunization, medical student engagement, community outreach, vaccine uptake, Pakistan, cross-sectional study